Venture deals : be smarter than your lawyer and venture capitalist - Feld, Brad, 4 0 16; 1971- Mendelson, Jason; 5 (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
Get the inside scoop on what venture capitalists want to see in your startup Venture Deals provides entrepreneurs and startup owners with a definitive reference for understanding venture capital funding. More than an overview of the process, this book delves into the details of the term sheet, the players, the negotiations, the legalities, and more, including what not to do. This new third edition has been updated to reflect the new realities of today's intricate startup environment: you'll learn how the decisions are made, what every item on the term sheet means, what's up for negotiation, and what's not. You'll discover the secrets to expanding your prospects, negotiating the right deal for your company, and figuring out the right balance of funding versus control. You'll see the process through the eyes of the venture capitalist, the angel investor, the syndicate, and the lawyer, and develop a strategy that makes funding your company a win for all parties involved. This book is designed to help entrepreneurs succeed, by bringing transparency to the venture capital funding process. Veteran investors walk you through the process from start to finish and beyond to help you: Understand how venture capital funds work, and how investors decide to invest Learn effective negotiation tactics based on game theory Delve into the meanings behind the term sheet's economic and control issues Avoid common issues that sink deals at the seed, early, mid- and late stages Written by the experts at Foundry Group, this unique guide is expressly geared toward those on the other side of the table; instead of parsing investor-focused advice and working backward, you get actual insider information on what the people with the money want to see. If you're ready to take the next step for your business, Venture Deals is an essential read--;In this updated Venture Deals, Third Edition, they will use their years of experience in venture capital and early stage investing to show entrepreneurs how to succeed and prosper, outlining the essential elements of the venture capital term sheet and the tactics needed to negotiate--
Introduction: The Art of the Term Sheet -- The Players -- How to Raise Money -- Overview of the Term Sheet -- Economic Terms of the Term Sheet -- Control Terms of the Term Sheet -- Other Terms of the Term Sheet -- The Capitalization Table -- Convertible Debt -- Crowdfunding -- How Venture Capital Funds Work -- Negotiation Tactics -- Raising Money the Right Way -- Issues at Different Financing Stages -- Letters of Intent The Other Term Sheet -- Why Do Term Sheets Even Exist? -- Legal Things Every Entrepreneur Should Know -- Authors' Note -- Foreword to the First and Second Editions.
Previous edition issued in print: 2013.
Description based on CIP data; resource not viewed.
Keywords: 2 -- 0; 6; Finance. -- Venture capital.;New business enterprises -- 20; 20; 2